A high-hardness wear-resistant coating and preparation method thereof

By using polyester modified acrylic resin in wear-resistant coatings with modified silicon carbide powder, reconditioning functional agent and other raw materials, the problems of poor adhesion and impact performance of existing wear-resistant coatings are solved, high hardness, wear resistance and good weather resistance are achieved, and product utilization efficiency is improved.

CN119775841AActive Publication Date: 2025-04-08GUANGDONG ORIENT RESIN
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510278953.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

While improving wear resistance and hardness, existing wear-resistant coatings can easily lead to poor adhesion and impact performance, and poor weather resistance and stability, which limits the efficiency of the product.

Method used

The combination of polyester modified acrylic resin with modified silicon carbide powder, re-adjustment functional agent and other raw materials is used to enhance the wear resistance, impact and adhesion of the coating, and improve weathering stability through ultrasonic treatment and ball milling treatment.

Benefits of technology

The high hardness and wear resistance of the coating are achieved, while improving adhesion and impact performance, significantly improving the product's weather resistance and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of wear-resistant coatings, and in particular to a high-hardness wear-resistant coating and a preparation method thereof, comprising the following raw materials in parts by weight: 40-45 parts of polyester-modified acrylic resin, 8-12 parts of modified silicon carbide powder, 4-7 parts of a re-adjusting functional agent, 2-5 parts of sodium carboxymethyl cellulose, 2-4 parts of m-phenylenediamine curing agent, 20-25 parts of toluene solvent, and 1-3 parts of stearic acid. The wear-resistant coating of the present invention adopts polyester-modified acrylic resin to match m-phenylenediamine curing agent, toluene solvent, stearic acid, sodium carboxymethyl cellulose, and simultaneously reconciles modified silicon carbide powder and a re-adjusting functional agent, and the two cooperate with each other to enhance the wear resistance, impact and adhesion coordination improvement of the product, and the weathering stability of the product has a remarkable effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant coatings, and in particular to a high-hardness wear-resistant coating and a preparation method thereof. Background Art

[0002] Wear-resistant coatings are a new type of functional coatings with special functions and good wear resistance. The machinery industry uses wear-resistant functional coating technology to treat the metal surface coating of key mechanical parts, which can improve the wear resistance, hardness and service life of mechanical equipment.

[0003] In order to enhance the wear resistance of products, existing coatings easily lead to poor adhesion and impact performance of products. It is difficult to coordinate and improve the wear resistance, impact and adhesion of products, and the weathering stability of products is poor, which limits the efficiency of product use. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high-hardness wear-resistant coating and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high-hardness wear-resistant coating, comprising the following raw materials in parts by weight: 40-45 parts of polyester modified acrylic resin, 8-12 parts of modified silicon carbide powder, 4-7 parts of adjusting agent, 2-5 parts of sodium carboxymethyl cellulose, 2-4 parts of m-phenylenediamine curing agent, 20-25 parts of toluene solvent, 1-3 parts of stearic acid; The preparation method of polyester modified acrylic resin is: 320g of hexylene glycol, 700g of neopentyl glycol, 600g of 1,4-cyclohexanedimethanol, 370g of trimellitic anhydride, 100g of hexahydrophthalic anhydride, 500g of 1,4-cyclohexanedicarboxylic acid, 550g of isophthalic acid, 130g of maleic anhydride, and 8g of antimony glycol were put into a reactor equipped with an agitator, a thermometer, a distillation column, a condenser and a nitrogen inlet. The reaction temperature was 250°C, the pressure was 0.12MPa, and the mixture was stirred for 6 hours. The pressure was adjusted to -0.095MPa, the reaction temperature was 200°C, the mixture was stirred for 3 hours, and the acid value viscosity was measured by sampling. The mixture was reacted until the acid value reached 25 mgKOH / g, and the temperature was lowered to 120°C. 1780 g of ethylene glycol monobutyl ether was added to adjust the solid content to 60±2%. The viscosity was measured by a rotary viscometer at 25°C to be 1500-3500 mPa.s, the unsaturation (expressed by iodine value, based on non-volatile matter) was 9.2, and the glass transition temperature was 5°C. The unsaturated polyester was obtained. 150g of the unsaturated polyester synthesized above, 320g of propylene glycol monobutyl ether, and 340g of ethylene glycol monobutyl ether are put into a reactor at a reaction temperature of 135-140°C; 15g of tert-butyl peroxybenzoate and 10g of tert-butyl peroxy 2-ethylhexanoate, 80g of methyl methacrylate, 120g of cyclohexyl methacrylate, 150g of isooctyl acrylate, 50g of ethyl acrylate, 350g of hydroxyethyl acrylate, and 70g of itaconic acid are uniformly mixed in a header tank and added dropwise to the reactor for 3 hours. The temperature is controlled at 135-140°C during the addition. After the monomer and initiator are dripped, the temperature is kept at 135-140°C for 2 hours, and the temperature is cooled to below 50°C. After 721g of deionized water and 109g of triethylamine are added and stirred for 30 minutes, the polyester-modified water-based acrylic resin is obtained by filtration; The preparation method of modified silicon carbide powder is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: adding 2-5 parts by weight of magnesium aluminum spinel and 1-3 parts by weight of magnesium oxide to 6-8 parts by weight of sodium citrate solution, and then adding 1-2 parts by weight of sodium dodecylbenzene sulfonate, stirring sufficiently, and then washing with water and drying to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, modified silicon carbide powder is obtained.

[0006] Preferably, the high hardness wear-resistant coating comprises the following raw materials in parts by weight: 42.5 parts of polyester modified acrylic resin, 10 parts of modified silicon carbide powder, 5.5 parts of replenishing functional agent, 3.5 parts of sodium carboxymethyl cellulose, 3 parts of m-phenylenediamine curing agent, 22.5 parts of toluene solvent, and 2 parts of stearic acid.

[0007] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 750-850r / min, and the ball milling is 2h.

[0008] Preferably, the mass fraction of the sodium citrate solution is 3-6%.

[0009] Preferably, the silane coupling liquid is prepared by fully stirring a silane coupling agent KH560 and a chitosan solution in a weight ratio of 2:5.

[0010] Preferably, the mass fraction of the chitosan solution is 2-5%.

[0011] Preferably, the preparation method of the tonic functional agent is: S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 2-4 parts by weight of glass fiber and 1-3 parts by weight of nano-silica sol to 3-6 parts by weight of lanthanum chloride solution, and then adding 2-3 parts by weight of zinc oxide, stirring sufficiently to obtain a regulated solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

[0012] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the stirring speed of the stirring treatment is 750-850r / min, and the stirring is 20-30min.

[0013] The present invention also provides a method for preparing a high-hardness wear-resistant coating, comprising the following steps: weighing raw materials according to weight, and mixing the raw materials to obtain the high-hardness wear-resistant coating.

[0014] Preferably, the hot pressing treatment pressure is 5 MPa.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The wear-resistant coating of the present invention adopts polyester modified acrylic resin, m-phenylenediamine curing agent, toluene solvent, stearic acid, sodium carboxymethyl cellulose, and simultaneously blends modified silicon carbide powder and a supplementary functional agent. The two cooperate with each other to enhance the wear resistance, impact and adhesion of the product, and the weathering stability of the product is remarkable. The modified silicon carbide powder is immersed in a sufficient amount of silane coupling liquid for ultrasonic treatment. The silane coupling liquid is prepared by stirring a silane coupling agent KH560 and a chitosan solution in a weight ratio of 2:5, so that the silicon carbide powder is better coordinated with the additives. The additive is a mixture of magnesium aluminum spinel, magnesium oxide, sodium citrate solution and sodium dodecylbenzene sulfonate. The coordination of the raw materials is used to enhance the coordination of system performance. The adjusting functional agent uses nano-alumina as the matrix raw material. The active efficiency of the raw materials is stimulated by irradiation in a proton irradiation box. The glass fiber, nano-silica sol, lanthanum chloride solution and zinc oxide are fully stirred to obtain an adjusting liquid. The raw materials in the adjusting liquid cooperate with each other to further coordinate the nano-alumina, so that the synergistic effect of the adjusting functional agent and the modified silicon carbide powder is enhanced, and the performance of the product is further improved. DETAILED DESCRIPTION

[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] A high-hardness wear-resistant coating of this embodiment includes the following raw materials in parts by weight: 40-45 parts of polyester modified acrylic resin, 8-12 parts of modified silicon carbide powder, 4-7 parts of adjusting functional agent, 2-5 parts of sodium carboxymethyl cellulose, 2-4 parts of m-phenylenediamine curing agent, 20-25 parts of toluene solvent, and 1-3 parts of stearic acid.

[0018] The high hardness wear-resistant coating of this embodiment comprises the following raw materials in parts by weight: 42.5 parts of polyester modified acrylic resin, 10 parts of modified silicon carbide powder, 5.5 parts of replenishing functional agent, 3.5 parts of sodium carboxymethyl cellulose, 3 parts of m-phenylenediamine curing agent, 22.5 parts of toluene solvent, and 2 parts of stearic acid.

[0019] The preparation method of the modified silicon carbide powder of this embodiment is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: adding 2-5 parts of magnesium aluminum spinel and 1-3 parts of magnesium oxide to 6-8 parts of sodium citrate solution, and then adding 1-2 parts of sodium dodecylbenzene sulfonate, stirring sufficiently, and then washing with water and drying to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, modified silicon carbide powder is obtained.

[0020] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 750-850r / min, and the ball milling is 2h.

[0021] The mass fraction of the sodium citrate solution of the present embodiment is 3-6%.

[0022] The silane coupling liquid of this embodiment is prepared by mixing silane coupling agent KH560 and chitosan solution in a weight ratio of 2:5.

[0023] The mass fraction of the chitosan solution in this embodiment is 2-5%.

[0024] The preparation method of the tonic functional agent of this embodiment is: S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 2-4 parts of glass fiber and 1-3 parts of nano-silica sol to 3-6 parts of lanthanum chloride solution, and then adding 2-3 parts of zinc oxide, stirring well, to obtain a conditioning solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

[0025] The mass fraction of the lanthanum chloride solution of the present embodiment is 3-5%; the stirring speed of the stirring process is 750-850r / min, and the stirring is 20-30min.

[0026] The preparation method of a high-hardness wear-resistant coating of the present embodiment comprises the following steps: weighing raw materials according to weight portions, and mixing the raw materials to obtain the high-hardness wear-resistant coating.

[0027] The heat pressing treatment pressure in this embodiment is 5 MPa.

[0028] Example 1.

[0029] A high-hardness wear-resistant coating of this embodiment includes the following raw materials in parts by weight: 40 parts of polyester modified acrylic resin, 8 parts of modified silicon carbide powder, 4 parts of replenishing functional agent, 2 parts of sodium carboxymethyl cellulose, 2 parts of m-phenylenediamine curing agent, 20 parts of toluene solvent, and 1 part of stearic acid.

[0030] The preparation method of the modified silicon carbide powder of this embodiment is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: Add 2 parts of magnesium aluminum spinel and 1 part of magnesium oxide to 6 parts of sodium citrate solution, then add 1 part of sodium dodecylbenzene sulfonate, stir thoroughly, then wash with water and dry to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, modified silicon carbide powder is obtained.

[0031] Preferably, the ultrasonic power of the ultrasonic treatment is 350W, and the ultrasonic time is 20min; the ball milling speed of the mixing ball milling treatment is 750r / min, and the ball milling is 2h.

[0032] The mass fraction of the sodium citrate solution in this embodiment is 3%.

[0033] The silane coupling liquid of this embodiment is prepared by mixing silane coupling agent KH560 and chitosan solution in a weight ratio of 2:5.

[0034] The mass fraction of the chitosan solution in this embodiment is 2%.

[0035] The preparation method of the tonic functional agent of this embodiment is: S11: irradiating the nano-alumina in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 2 parts of glass fiber and 1 part of nano-silica sol to 3 parts of lanthanum chloride solution, and then adding 2 parts of zinc oxide, stirring well to obtain a conditioning solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

[0036] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the stirring speed of the stirring process is 750r / min, and the stirring is 20min.

[0037] The preparation method of a high-hardness wear-resistant coating of the present embodiment comprises the following steps: weighing raw materials according to weight portions, and mixing the raw materials to obtain the high-hardness wear-resistant coating.

[0038] The heat pressing treatment pressure in this embodiment is 5 MPa.

[0039] Example 2.

[0040] A high-hardness wear-resistant coating of this embodiment includes the following raw materials in parts by weight: 45 parts of polyester modified acrylic resin, 12 parts of modified silicon carbide powder, 7 parts of replenishing functional agent, 5 parts of sodium carboxymethyl cellulose, 4 parts of m-phenylenediamine curing agent, 25 parts of toluene solvent, and 3 parts of stearic acid.

[0041] The preparation method of the modified silicon carbide powder of this embodiment is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: adding 5 parts of magnesium aluminum spinel and 3 parts of magnesium oxide to 8 parts of sodium citrate solution, and then adding 2 parts of sodium dodecylbenzene sulfonate, stirring thoroughly, and then washing with water and drying to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, modified silicon carbide powder is obtained.

[0042] Preferably, the ultrasonic power of the ultrasonic treatment is 400 W, and the ultrasonic time is 30 min; the ball milling speed of the mixing ball milling treatment is 850 r / min, and the ball milling is 2 h.

[0043] The mass fraction of the sodium citrate solution in this embodiment is 6%.

[0044] The silane coupling liquid of this embodiment is prepared by mixing silane coupling agent KH560 and chitosan solution in a weight ratio of 2:5.

[0045] The mass fraction of the chitosan solution in this embodiment is 5%.

[0046] The preparation method of the tonic functional agent of this embodiment is: S11: irradiating the nano-alumina in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 4 parts of glass fiber and 3 parts of nano-silica sol to 6 parts of lanthanum chloride solution, and then adding 3 parts of zinc oxide, stirring well to obtain a conditioning solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

[0047] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the stirring speed of the stirring process is 850r / min, and the stirring is 30min.

[0048] The preparation method of a high-hardness wear-resistant coating of the present embodiment comprises the following steps: weighing raw materials according to weight portions, and mixing the raw materials to obtain the high-hardness wear-resistant coating.

[0049] The heat pressing treatment pressure in this embodiment is 5 MPa.

[0050] Example 3.

[0051] A high-hardness wear-resistant coating of this embodiment includes the following raw materials in parts by weight: 42.5 parts of polyester modified acrylic resin, 10 parts of modified silicon carbide powder, 5.5 parts of replenishing functional agent, 3.5 parts of sodium carboxymethyl cellulose, 3 parts of m-phenylenediamine curing agent, 22.5 parts of toluene solvent, and 2 parts of stearic acid.

[0052] The preparation method of the modified silicon carbide powder of this embodiment is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: adding 3.5 parts of magnesium aluminum spinel and 2 parts of magnesium oxide to 7 parts of sodium citrate solution, and then adding 1.5 parts of sodium dodecylbenzene sulfonate, stirring thoroughly, and then washing with water and drying to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, modified silicon carbide powder is obtained.

[0053] Preferably, the ultrasonic power of the ultrasonic treatment is 370W, and the ultrasonic time is 25min; the ball milling speed of the mixing ball milling treatment is 800r / min, and the ball milling is 2h.

[0054] The mass fraction of the sodium citrate solution in this embodiment is 4.5%.

[0055] The silane coupling liquid of this embodiment is prepared by mixing silane coupling agent KH560 and chitosan solution in a weight ratio of 2:5.

[0056] The mass fraction of the chitosan solution in this embodiment is 3.5%.

[0057] The preparation method of the tonic functional agent of this embodiment is: S11: irradiating the nano-alumina in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 3 parts of glass fiber and 2 parts of nano-silica sol to 4.5 parts of lanthanum chloride solution, and then adding 2.5 parts of zinc oxide, stirring well, to obtain a conditioning solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

[0058] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the stirring speed of the stirring process is 800r / min, and the stirring is 25min.

[0059] The preparation method of a high-hardness wear-resistant coating of the present embodiment comprises the following steps: weighing raw materials according to weight portions, and mixing the raw materials to obtain the high-hardness wear-resistant coating.

[0060] The heat pressing treatment pressure in this embodiment is 5 MPa.

[0061] Comparative Example 1. The difference from Example 3 is that no modified silicon carbide powder is added.

[0062] Comparative Example 2. The difference from Example 3 is that the modified silicon carbide powder is not treated with silicon carbide coupling and silane coupling liquid.

[0063] Comparative Example 3. The difference from Example 3 is that the silicon carbide coupling and silane coupling liquid are replaced by a silane coupling agent aqueous solution with a mass fraction of 5%.

[0064] Comparative Example 4. The difference from Example 3 is that no additive treatment is used in the modified silicon carbide powder.

[0065] Comparative Example 5. The difference from Example 3 is that the preparation method of the additive is different; Add 2 parts of magnesium oxide to 7 parts of sodium citrate solution and stir well to obtain an additive.

[0066] Comparative Example 6. The difference from Example 3 is that no replenishing functional agent is added.

[0067] Comparative Example 7. The difference from Example 3 is that no regulating liquid treatment is used in the preparation of the replenishing and regulating functional agent.

[0068] Comparative Example 8. The difference from Example 3 is that glass fiber and zinc oxide are not added to the conditioning solution.

[0069] The conventional performance tests of the products of Examples 1-3 and Comparative Examples 1-8 were carried out by irradiating with a 280nm UV lamp for 10 hours at an irradiation intensity of 100mj / m 2 , the test is as follows:

[0070] It can be seen from Comparative Examples 1-8 and Example 3 that the product of Example 3 has excellent adhesion, wear resistance, impact resistance and hardness performance, and the product performance is coordinated and improved, and the product weathering stability effect is remarkable; The present invention does not add modified silicon carbide powder and does not add a supplementary functional agent, and the performance of the product has an obvious tendency to deteriorate. The two are coordinated and cooperated, and the product performance effect is most obvious; the modified silicon carbide powder is not treated with silicon carbide and silane coupling liquid, the silicon carbide and silane coupling liquid are replaced by a silane coupling agent aqueous solution with a mass fraction of 5%, the modified silicon carbide powder is not treated with additives, and the additive preparation method is different. The performance of the product has a tendency to deteriorate. Only the modified silicon carbide powder obtained by the method of the present invention has the most significant product performance effect. In addition, the preparation of the supplementary functional agent does not use the adjustment liquid treatment, and glass fiber and zinc oxide are not added to the adjustment liquid. The performance of the product also shows a tendency to deteriorate. The adjustment liquid obtained by the specific method of the present invention has the most significant product performance effect.

[0071] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0072] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high hardness wear-resistant coating, characterized in that: It comprises the following raw materials in parts by weight; 40-45 parts of polyester modified acrylic resin, 8-12 parts of modified silicon carbide powder, 4-7 parts of adjusting agent, 2-5 parts of sodium carboxymethyl cellulose, 2-4 parts of m-phenylenediamine curing agent, 20-25 parts of toluene solvent, 1-3 parts of stearic acid; The preparation method of modified silicon carbide powder is: S01: immersing silicon carbide powder in a sufficient amount of silane coupling liquid for ultrasonic treatment, and then completing the ultrasonic treatment to obtain silicon carbide coupling and silane coupling liquid; S02: adding 2-5 parts by weight of magnesium aluminum spinel and 1-3 parts by weight of magnesium oxide to 6-8 parts by weight of sodium citrate solution, and then adding 1-2 parts by weight of sodium dodecylbenzene sulfonate, stirring sufficiently, and then washing with water and drying to obtain an additive; S03: The additive, silicon carbide and silane coupling liquid are mixed and ball-milled in a weight ratio of 5:

3. After the ball-milling is completed, modified silicon carbide powder is obtained.

2. A high hardness wear-resistant coating according to claim 1, characterized in that: The high hardness wear-resistant coating comprises the following raw materials in parts by weight: 42.5 parts of polyester modified acrylic resin, 10 parts of modified silicon carbide powder, 5.5 parts of replenishing functional agent, 3.5 parts of sodium carboxymethyl cellulose, 3 parts of m-phenylenediamine curing agent, 22.5 parts of toluene solvent, and 2 parts of stearic acid.

3. A high hardness wear-resistant coating according to claim 1, characterized in that: The ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 750-850r / min, and the ball milling is 2h.

4. A high hardness wear-resistant coating according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 3-6%.

5. The high hardness wear-resistant coating according to claim 1, characterized in that: The silane coupling liquid is prepared by fully stirring a silane coupling agent KH560 and a chitosan solution in a weight ratio of 2:

5.

6. A high hardness wear-resistant coating according to claim 5, characterized in that: The mass fraction of the chitosan solution is 2-5%.

7. A high hardness wear-resistant coating according to claim 1, characterized in that: The preparation method of the tonic functional agent is as follows: S11: irradiating the nano-alumina in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated nano-alumina after the irradiation is completed; S12: adding 2-4 parts by weight of glass fiber and 1-3 parts by weight of nano-silica sol to 3-6 parts by weight of lanthanum chloride solution, and then adding 2-3 parts by weight of zinc oxide, stirring sufficiently to obtain a regulated solution; The irradiated nano-alumina and the regulating liquid are stirred at a weight ratio of 2:

5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a replenishing and regulating functional agent.

8. A high hardness wear-resistant coating according to claim 7, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the stirring speed of the stirring treatment is 750-850r / min, and the stirring is performed for 20-30min.

9. A method for preparing a high-hardness wear-resistant coating as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed according to weight portions, and the raw materials are mixed thoroughly to obtain a high-hardness wear-resistant coating.

Citation Information

Patent Citations

  • High-temperature (800 DEG C) wear-resistant paint and preparation method thereof

    CN104004435A

  • Composite refractory material and preparation method thereof

    CN117756541A

  • High-temperature-resistant fireproof coating powder and preparation method thereof

    CN118772744A

  • Hard alloy drill bit and preparation method

    CN118951021A

  • A composition of protecting metal surface and method for execution of metallic structure using thereof

    KR102088839B1